Scientific Writing Training as an Effort to Improve Literacy - Rifky Maulana Yusron; Rica Wijayanti; Zainudin Zainudin; Heni Yuli Handayani; Yusrianto Sholeh (Universitas Nurul Jadid, 2024)
literacy rate, evidenced by the minimal number of written works produced by its residents. To address this issue, particularly among educators and students, we proposed a community service program aimed at enhancing literacy skills in scientific writing. This program was designed to provide socialization and assistance in writing for students and educators in one of the schools in Bangkalan Regency. The objective of this community service program is to improve the scientific writing skills of educators and students. The implementation process begins with socialization sessions covering the necessary preparations for writing scientific works, essential elements of scientific writing, and the use of Mendeley. These socialization sessions were conducted three times, followed by a mentoring process where our team assisted participants until they produced scientific papers ready for publication. The community service program concluded with participants completing a questionnaire to evaluate their responses to the program. As a result of these activities, ten written works were produced, ready for publication in journals or print media. Questionnaire results indicate that 95% of participants felt motivated to write scientific papers, and 100% responded positively to the community service activities.